Description of maxillary sinus height and width in partial edentulous and full edentulous patients - Nurrahman, Tri; Sarifah, Norlaila; Latifah, Ananda Putri; Azizah, Aulia; Sari, Rima Permata; Sukmana, Bayu Indra (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This research aims to determine the height and width of the maxillary sinus in partial edentulous and full edentulous patients using panoramic radiographs at RSUD Ulin and RSGM Gusti Hasan Aman Banjarmasin. Materials and Methods: This research was conducted using a descriptive approach with a cross-sectional method, involving 105 samples that met the inclusion and exclusion criteria through purposive sampling. The research samples consisted of digital panoramic radiograph archives of patients aged 21-80 years from RSUD Ulin and RSGM Gusti Hasan Aman Banjarmasin, recorded in the Radiology Department. Results: The result showed that the highest average maxillary sinus height was found in full edentulous patients, measuring 32.840 ± 5.652 mm, while the lowest average height was found in partial edentulous patients classified as Kennedy Class IV, measuring 30.736 ± 5.479 mm. The largest average maxillary sinus width was found in partial edentulous patients classified as Kennedy Class I, measuring 35.905 ± 6.576 mm, while the smallest average width was found in full edentulous patients, measuring 31.911 ± 6.342 mm. Conclusion: The highest average maxillary sinus height was found in full edentulous patients, while the highest average maxillary sinus width was found in partial edentulous patients with Kennedy Class I classification. Conversely, the lowest average maxillary sinus height was found in partial edentulous patients with Kennedy Class IV, and the smallest average maxillary sinus width was found in full edentulous patients.